Cavitation erosion behavior of HVOF sprayed WC-10Co4Cr cermet coatings in simulated sea water. (15th October 2019) - Liu, Xiao-bin; Kang, Jia-jie; Yue, Wen; Ma, Guo-zheng; Fu, Zhi-qiang; Zhu, Li-na; She, Ding-shun; Liang, Jian; Weng, Wei; Wang, Hai-dou; Wang, Cheng-biao
Abstract: Mechanical equipment operating in the ocean is vulnerable to cavitation erosion damage. The coatings fabricated by high velocity oxygen fuel (HVOF) spraying technology can remarkably improve the resistance of cavitation erosion. In this study, WC-10Co4Cr coatings with two structures (conventional and bimodal) were prepared on 35CrMo steel substrate, respectively. The morphologies and structures of the powders and as-sprayed coatings were analyzed by SEM and XRD, and microhardness, porosity and surface roughness were also studied. The corrosion resistance of the coatings was evaluated by using potentiodynamic polarization. More importantly, the cavitation erosion resistance in simulated sea water was studied by the ultrasonic cavitation vibratory apparatus and the cavitation erosion failure mechanisms were also explored. The results show that the bimodal coating has better quality and cavitation erosion resistance. Moreover, the effect of corrosion on cavitation erosion is not obvious. Highlights: The bimodal structure coatings exhibit superior quality and mechanical properties than conventional coatings. The cavitation erosion resistance of the bimodal structure coating is better than that of conventional coating. The effect of corrosion on cavitation is not obvious under experimental conditions. The main cavitation failure mechanism is the spalling caused by crack under the impact of bubble burst.